STRATEGI PEMASARAN KOPERASI BINA USAHA AL-IHSAN: MARKETINGSTRATEGY OF BINA USAHA AL-IHSAN COOPERATIVE - Raja Sharah Fatricia; Layra Nichi Sari (DIGEST MARKETING, 2018)
Mangosteenis atropicalfruitcommoditiesoriginatingfrom the NusantaraIslands. West Javais one ofthe biggestmangosteenfruitproducer inIndonesia wheere KBUAl-Ihsan is one of thecooperativesenvolped. The problem existedwith the cooperative; 70percent ofthe mangosteen fruit quality is poor and 30has export quality. The excess of rejecting fruitis the main reason thatcooperative is in need to developsomestrategiesto marketthe fruit.The purposeof this studyis management developa reliable marketing strategyforthe KBU Al-Ihsan based oninternaland externalenvironmentalfactors,andformulatealternativemarketingstrategiesadoptedby KBU Al-Ihsan based ona scientific approach. This researchusesanalysis toolInternalFactorMatrixevalution(IFE), the matrix ExternalFactorevalution(EFE), and strenghts, Weaknesees, Opportunities,andThreats(SWOT). Keyword: mangosteenmarketing strategies, IFEMatrix, EFEMatrix, andSWOTmatrix..